Effects of monsoon trough interannual variation on tropical cyclogenesis over the western North Pacific. Issue 12 (17th June 2014) - Cao, Xi; Li, Tim; Peng, Melinda; Chen, Wen; Chen, Guanghua
Abstract The western North Pacific monsoon trough (MT) exhibits marked interannual variation (IAV) associated with El Niño–Southern Oscillation forcing. The role of MT IAV in tropical cyclone (TC) development was investigated using the Advanced Research Weather Research and Forecasting model placed on a beta plane. It was found that MT IAV has a great influence on vortex development. In strong years, the MT provides more favorable environmental conditions—primarily through enhanced low‐level vorticity, convergence and midlevel moisture—for TC formation and vice versa in weak years. Sensitivity experiments that separated the dynamic and thermodynamic (moisture) factors from strong MT IAV showed that the thermodynamic impact associated with MT IAV is comparable to the dynamic impact.